Response to aerosol salbutamol, SCH 1000, and placebo in cystic fibrosis. Issue 7 (July 1980) - Kattan, M; Mansell, A; Levison, H; Corey, M; Krastins, I R
Abstract : The responses of 20 patients with cystic fribrosis to a B2 agonist, salbutamol, to an anticholinergic agent, SCH 1000, and to a placebo containing difluorodichloroethane and soya lecithin delivered by metered aerosol were compared. Flow rates decreased significantly after placebo (p < 0.05). FEV1 increased significantly after salbutamol (p < 0.05), but the degree of these changes was small. There was a small but significant increase in FVC but no change in flow rates after SCH 1000. Specific conductance increased significantly (p < 0.01) after both salbutamol and SCH 1000. Thoracic gas volume remained unchanged with both drugs and placebo. Four of 20 patients had a clinically significant increase in flow rates with SCH 1000 and three with salbutamol. The consistent increases in sGaw coupled with minimal changes in flow rates, suggest that the physiological effects of both agents is to increase the compressibility of the airway. The results after placebo demonstrate the increased airway reactivity to irritants in cystic fibrosis. In view of this, attention should be paid to the possible irritant effects of inhaled medications.